1994
DOI: 10.1143/jjap.33.l722
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Voltage of High Tc DC Superconducting Quantum Interference Device with Damping Resistance

Abstract: The effect of damping resistance on the voltage versus flux (V -Φ) relation of the high T c dc superconducting quantum interference device (SQUID) is studied experimentally. Dc SQUID using YBaCuO step-edge junction and damping resistance in parallel with SQUID inductance is fabricated. Measured values of modulation voltage in the V -Φ relation are compared with those of the conventional SQUID without damping resistance. It is shown that modulation voltage is much improved by using damping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Four-junction SQUID configurations were previously discussed theoretically in the context of control of the critical current [34] and of current amplification in micronetworks [35]; however, the shift of the interference pattern and the problem of blind spots has not been addressed. Several other multi-junction or multi-terminal configurations, which provide various functionalities and flux bias of the SQUID, have been studied in the past [7,32,[36][37][38][39][40][41]. The recently described 2-junction 4-terminal SQUID [42] shares the ability of the hereby described mSQUID to control the interference pattern externally without substantially affecting the flux in the SQUID loop.…”
Section: Introductionmentioning
confidence: 99%
“…Four-junction SQUID configurations were previously discussed theoretically in the context of control of the critical current [34] and of current amplification in micronetworks [35]; however, the shift of the interference pattern and the problem of blind spots has not been addressed. Several other multi-junction or multi-terminal configurations, which provide various functionalities and flux bias of the SQUID, have been studied in the past [7,32,[36][37][38][39][40][41]. The recently described 2-junction 4-terminal SQUID [42] shares the ability of the hereby described mSQUID to control the interference pattern externally without substantially affecting the flux in the SQUID loop.…”
Section: Introductionmentioning
confidence: 99%
“…Measured values of for each SQUID are listed in Table I. For comparison, the expected values for SQUIDs without damping resistance given by Enpuku et al in [8]: (3) are also shown in this Table. The ratio of to is 0.4-0.7 and is independent of the value of the damping resistance. Hence we cannot confirm any suppression of the resonance phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…It has been already reported that degradation of due to large SQUID inductances can be recovered when the damping resistance, which is regarded as a lump component, is introduced [3]- [5]. In this paper, first, we show results of numerical simulations for the damping effect by a lump circuit model.…”
mentioning
confidence: 96%